Effect of eWOM, Ease of Use, Trust on Purchase Decision (Case Study on Blibli.com) - Angel, Vivian; Natadirja, Moses (Jurnal Manajemen, 2021)
The purpose of this study was to determine: 1) Whether eWOM has a positive effect on purchase decisions, 2) Does Ease of Use have a positive effect on purchase decisions, 3) Does trust have a positive effect on purchase decisions. Data collection in this study was carried out using a questionnaire distributed online to Blibli users. The number of respondents used in this study is 100 respondents. The sampling technique used in this study is non-probability sampling by relying on judgmental sampling. Partial least square-structural equation modeling (PLS-SEM) analysis was performed using the SmartPLS 3.0 program to analyze the data. The findings of this study are that eWOM, Ease of Use and Trust have a positive effect on purchase decisions. The contribution of this research can provide input to the Blibli company to better maintain and manage ease of use, trust and electronic word of mouth so that Blibli users can use Blibli more freely and comfortably so that transactions carried out in Blibli can run more smoothly and safely, which is then will give Blibli an advantage as a player in Internet-based transaction systems because it is a fast paced industries that can change in a matter of time.